First Farmers in the South China Coast: New Evidence From the Gancaoling Site of Guangdong Province - Deng, Zhenhua; Huang, Bixiong; Zhang, Qianglu; Zhang, Min (Frontiers in Earth Science, 2022)
The transformation from hunter-gathering to farming in the south China coast has always been a conspicuous topic, as its great significance for the understanding of crop dispersal and human migration into southern China and Southeast Asia. It has been primarily assumed that rice was the only crop cultivated by early farmers in this region since 5,000 cal. BP., but the reliability of this speculation remains ambiguous, owing to the lack of systematic evidence. Based on analysis of macroscopic plant remains and phytoliths, as well as AMS radiocarbon dating at the Gancaoling site in Guangdong province, this study demonstrates the emergence of agriculture in the south China coast could be dated back to as early as 4800-4600 cal. BP., with the cultivation of rice and foxtail millet. This subsistence strategy change was an integral part of a more comprehensive social transformation, which started a new era of local history. Moreover, this discovery also provides further evidence supporting the universality of mixed farming in southern China and shed new light on the study of agriculture southward dispersal. The crop package of rice and millets possibly spread into the south China coast from Jiangxi via the mountain areas and then into Mainland Southeast Asia by a maritime route along the coastal regions.